Science, technology, engineering, agriculture, mathematics, and health in agribusiness curriculum - Ai Tusi Fatimah; Agus Yuniawan Isyanto; Toto Toto (Institute of Advanced Engineering and Science, 2023)
Vocational high school curriculum can provide various solutions to problems in the business and industrial worlds that require a variety of disciplines. The complex problem-solving in the real world has increased the multidisciplinary boundaries of science, technology, engineering, agriculture, mathematics, and health (STEAM-H). Therefore, this study investigated teachers’ understanding of the coherence and integration of the vocational high school curriculum in the crop agribusiness program in STEAM-H. The sample population consisted of science, mathematics, and productive teachers from a crop agribusiness vocational high school in Ciamis, Indonesia. The results showed that participants’ understanding of curriculum coherence began with the knowledge of the existence of conceptual connections between subjects, essential concepts, explicit or implicit, and concepts outside or within the curriculum. Furthermore, the productive teachers were more aware of implicit subject connections in this study. Teachers often had different points of view on the essential concepts listed in the curriculum. The results also showed that agriculture is a conceptual integrator for science, technology, engineering, mathematics, or health for integrated STEAM-H learning, as well as a contextual integrator for subject-centered education. The teachers argued that the multidisciplinary, interdisciplinary, and transdisciplinary patterns were suitable for implementation with strategies agreed upon across all subjects. Therefore, the understanding of teachers is expected to change integrated learning in crop agribusiness schools to an independent curriculum.